Preparation and properties of surface modified zeolite-based warm mix flame retardant modified asphalt - Yangwei Tan; Jianguang Xie; Jinwei Xu; Xiang Li; Zhaoyi He (Journal of Traffic and Transportation Engineering (English ed. Online))
To achieve environmentally friendly construction and safe operation of tunnel pavements, the mixing construction temperature of asphalt pavements needs to be reduced and the fire safety of asphalt pavements needs to be improved. In this paper, zeolite-based warm mix agent (WMA) and targeted flame retardants (TFR) were used for asphalt modification to reduce the mixing temperature and improve the fire safety of asphalt pavements. First, the formulation of zeolite-based warm mix flame retardant (WMFR) was optimized based on the response surface multi-satisfaction optimization method (RSMOM); then, three kinds of surface modifiers were used to surface modify for WMFR; finally, the functional properties and road performance of WMFR modified asphalt (WMFRMA) were investigated. The results showed that the surface modification could improve the compatibility and storage stability of WMFR with asphalt. The mixing temperature of Titanate coupling agent modified WMFR modified asphalt (Ti-WMFRMA) and surface active agent modified WMFR modified asphalt (Sur-WMFRMA) was reduced by about 10 °C compared with that of the matrix asphalt (JZ). But, there was no significant change in the mixing temperature of Silane coupling agent modified WMFR modified asphalt (Si-WMFRMA). The four kinds of WMFR could effectively improve the fire safety of asphalt binder and mixture. Among them, the peak heat release (PRR) of Sur-WMFRMA was 62.81% lower than that of JZ, and the peak smoke production (PSPR) of Ti-WMFRMA was 69.98% lower than that of JZ. The rheological properties of the flame retardant modified asphalt binder and the road performance of the asphalt mixture were verified, and the surface modification of WMFR could effectively improve the functional properties and road performance of asphalt.